Peran Bank Syariah dalam Mendorong Kewirausahaan di Masyarakat: Tinjauan Literatur terhadap Pembiayaan Syariah dan Edukasi Kewirausahaan UMKM - Qanaah, Qanaah; Muh. Zidni Syukran; Muliani, Muliani (Mutawasith: Jurnal Hukum Islam, 2025)
Entrepreneurship drives economic growth and job creation in Indonesia, particularly through Micro, Small, and Medium Enterprises (MSMEs). This literature review analyzes Islamic banks' contribution to entrepreneurship development through Sharia-based financing and entrepreneurship education programs. Using systematic literature review methodology, this study examines published articles, books, and research reports to integrate multiple perspectives on Islamic banks' economic and social impact. Findings reveal Islamic banks play a strategic role supporting MSMEs through Sharia financing products (mudharabah and musyarakah), offering more equitable and sustainable alternatives than conventional systems. Beyond capital access, Islamic banks provide training and mentoring in financial management, marketing, and product development, enabling entrepreneurs to manage businesses effectively. Islamic banks create sustainable, inclusive entrepreneurship ecosystems through Sharia-based financing and comprehensive education, reducing economic inequality, creating employment, and improving societal welfare aligned with Islamic financial values of justice and collaboration.